Resistance to diverse drugs and ultraviolet light conferred by overexpression of a novel human 26 S proteasome subunit. - Spataro, V; Toda, T; Craig, R; Seeger, M; Dubiel, W; Harris, A; Norbury, C (1997)
We have investigated the usefulness of the fission yeast Schizosaccharomyces pombe as a model organism for the discovery of novel modes of drug resistance in human cells. In fission yeast, overexpression of the essential pad1(+) gene confers pleiotropic drug resistance through a pathway involving an AP-1 transcription factor encoded by pap1(+). We have identified POH1, a human pad1 homologue that can substitute fully for pad1(+) and induce AP-1-dependent drug resistance in fission yeast. POH1 also confers P-glycoprotein-independent resistance to taxol (paclitaxel), doxorubicin, 7-hydroxystaurosporine, and ultraviolet light when transiently overexpressed in mammalian cells. Poh1 is a previously unidentified component of the human 26 S proteasome, a multiprotein complex that degrades proteins targeted for destruction by the ubiquitin pathway. Hence, Poh1 is part of a conserved mechanism that determines cellular susceptibility to cytotoxic agents, perhaps by influencing the ubiquitin-dependent proteolysis of transcription factors.